Implementation of Deep Assets Separation Agreement of Indonesian Citizens Who Marriage with Foreign Citizens - Bella Arwinilita; Gunarto Gunarto; Anis Mashdurohatun (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This study aims to analyze legal protection in the making of an agreement on the separation of assets in marriage between Indonesian citizens and foreign nationals and to analyze the authority of a notary on the making of an agreement on the separation of assets in marriage between Indonesian citizens and foreign citizens. This research uses empirical normative research. The approach method used is the statutory approach, conceptual approach and case approach. Based on the research results, it can be concluded that the making of a marriage agreement can provide legal protection for the parties who make it. The agreement deed made in a notary can be used as written evidence in court if problems occur in the future. Based on Article 1868 of the Civil Code and the authority of notaries in Article 15 of the UUJN, it states that notaries have the authority to make authentic deeds related to all agreements. Notaries must be able to provide legal certainty in people's lives because in the deed there is evidence that clearly determines the rights and obligations of a person as a legal subject in society. Notary Deed as a deed that has perfect evidentiary power makes the position of the Notary deed as the first and foremost evidence in civil evidentiary law.